A Comprehensive Overview of the Complex Role of Oxidative Stress in Aging, The Contributing Environmental Stressors and Emerging Antioxidant Therapeutic Interventions - Iakovou, Evripides; Kourti, Malamati (Frontiers in Aging Neuroscience, 2022)
Introduction: Aging is a normal, inevitable, irreversible and progressive process which is driven by internal and external factors. Oxidative stress, that is the imbalance between prooxidant and antioxidant molecules favoring the first, plays a key role in the pathophysiology of aging and comprises one of the molecular mechanisms underlying age-related diseases. However, the oxidative stress theory of aging has not been successfully proven in all animal models studying lifespan, meaning that altering oxidative stress/ antioxidant defense systems did not always lead to a prolonged lifespan, as expected. On the other hand, animal models of age-related pathological phenotypes showed a well-correlated relationship with the levels of prooxidant molecules. Therefore, it seems that oxidative stress plays a more complicated role than the one once believed and this role might be affected by the environment of each organism. Environmental factors such as UV radiation, air pollution and an unbalanced diet, have also been implicated in the pathophysiology of aging and seem to initiate this process more rapidly and even in younger ages. Aim: The purpose of this review is to elucidate the role of oxidative stress in the physiology of aging and the effect of certain environmental factors in initiating and sustaining this process. Understanding the pathophysiology of aging will contribute to the development of strategies to postpone this phenomenon. In addition, recent studies investigating ways to alter the antioxidant defense mechanisms in order to prevent aging will be presented. Conclusions: Careful exposure to harmful environmental factors and the use of antioxidant supplements could potentially affect the biological processes driving aging and slow down the development of age-related diseases. Maybe a prolonged lifespan could not be achieved by this strategy alone, but a longer healthspan could also be a favorable target.